Milk production capacity of priangan prolific sheep: II. The lactation curve - B Tiesnamurti; I Inounu; Subandriyo .; H Martojo (Indonesian Center for Animal Research and Development (ICARD), 2003)
A calculation was made for the lactation curve of Priangan sheep using Wood equation to find out how much differences actual milk production of uncorrected ewes compared to those corrected using parity and litter size born. Milk production was measured using weighing of the lambs before and shortly after suckling, with average of daily and total milk production were 519.5 g/head and 43.6 kg head-1 lactation-1, respectively. The average of parameter a, which reflected milk production at the beginning of the lactation period was 6.296 that equivalent to 571.5 g/head and significantly affected (P<0.05) by parity. The b parameter which reflected the rate of milk increment at the beginning of the lactation period was found to be 0.528 and significantly affected (P<0.05) by parity. The c parameter which reflected the rate of milk decline at the end of lactation period was found to be -0.20 and significantly affected (P<0.05) by parity. The average persistency which reflected the duration of maximum milk production was found to be 22.58 days without any significant contribution of parity and the number of lamb born. The average time to reach maximum milk production was found to be at week 3.5 after lambing without any significant contribution of parity and litter size. The average estimation of maximum milk production was 708.4 g/head and significantly affected (P<0.05) by ewe parity. Key words: Milk production, lactation curve, Priangan sheep